Giant Asteroid or Nuclear Winter - A 2023 Menu - Gurevitz, Michael (European Journal of Applied Sciences, 2023)
Human fears of the unknown and death have always been a major trigger in establishment of religions with eccentric rituals and customs, enabling delusive projection of their concerns on a heavenly creator (God). This mystic belief provided spiritual strength and elusive serenity (“life and death in his hands”), as well as an explanation for our existence as the ‘selected species’ in the alleged ‘center of the universe’. However, most rational people do not accept this ostensible perspective and prefer the scientific view that considers homo sapiens the top mammalian species in the evolutionary tree of the animal kingdom. In this view, the survival of the human species requires balanced relations with nature, and apt utilization of its resources.